2018
DOI: 10.1097/qai.0000000000001678
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Viremia Is Associated With Clinical Progression in HIV-Infected Patients Receiving Antiretroviral Treatment

Abstract: In this cohort, LLV200-499 was strongly associated with AIDS events/death and virological failure, but not with any serious NAE. Therefore, vigorous treatment should be implemented in patients with more than 200 copies per milliliter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
67
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 33 publications
14
67
4
Order By: Relevance
“…In contrast to previous studies, we focused only on the factors of high-risk LLV subgroup leading to VF, to identify conditions that need prompt treatment during ART. Although we used new definitions of LLV and VF, we found some similar risk factors as several resource-rich cohort studies, including the high zenith VL and low nadir CD4 + T cell counts [3,22,23]. In addition, we found that long-term ART, AZT + 3TC + NVP or DDI + NRTI+NNRTI regimens, Manchu and subtype B′ infection were all risk factors in this study.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In contrast to previous studies, we focused only on the factors of high-risk LLV subgroup leading to VF, to identify conditions that need prompt treatment during ART. Although we used new definitions of LLV and VF, we found some similar risk factors as several resource-rich cohort studies, including the high zenith VL and low nadir CD4 + T cell counts [3,22,23]. In addition, we found that long-term ART, AZT + 3TC + NVP or DDI + NRTI+NNRTI regimens, Manchu and subtype B′ infection were all risk factors in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Antiretroviral therapy (ART) can limit virus replication to less than 50 copies/ml and effectively prolong the life of HIV-1 infected patients [1]. However, in approximately 10-30% of the patients, depending on the definition, standard ART cannot control viral replication completely [2,3]. The plasma of such patients shows low level of viral replication, which is designated as low level viremia (LLV) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential contribution of LLV to clinical outcomes in PLHIV receiving long‐term ART, as well as the mechanisms involved, remains unclear. Increased mortality for LLV patients has been suggested , but has not been shown in other studies . Regarding cardiovascular risk, Zhang et al .…”
Section: Discussionmentioning
confidence: 88%
“…Although most PLHIV achieve stable suppression of viral replication during ART, persistent low‐level viraemia (LLV) occurs in some individuals. LLV has been associated with subsequent virological failure and emerging drug resistance , but the relationship between LLV and clinical endpoints is controversial . Recently, we reported a trend for increased mortality among Swedish PLHIV with LLV, with the main overall cause of death being CVD .…”
Section: Introductionmentioning
confidence: 96%